Post-Soviet studies: crisis of concepts, conventions, and compromises - Bogdanova, E; Dzenovska, D; Morris, J; Muravyeva, M; Pallot, J (Centre for Independent Social Research, 2023)
The roundtable is a response to the state of distress in which many researchers of postSoviet processes, spaces, and transformations found themselves after the start of the war in Ukraine in February 2022. The nature of this anguish can be found, first of all, in the realization of the irreversibility of the events. But it also captured social scientists’ professional sphere. The crisis of post-Soviet studies, which had already been discussed for a long time, has manifested itself in full force. Many of the foundational, widely accepted concepts that were used to explaine the post-Soviet transformations—and seemed dependable—have been discredited or called into question. The roundtable, which took place in Helsinki in October 2022, was not so naive as to seek to solve any problems. The discussion that took place was an attempt to feel out and confront the underlying concepts and assumptions that have failed, as well as an attempt to capture scholarly reflections on the difficult situation that we are living through now.